Analysis of the Problems Faced by Class VII Students in the Process of Implementing PJOK Learning at SMP Negeri 1 Batang Gansal - Rodika Novtu Hualri; Merlina Sari (Jurnal Olahraga Indragiri, 2023)
The purpose of this study was to find out the analysis of the problems faced by class VII students in the process of implementing PJOK learning at SMP Negeri 1 Batang Gansal. This type of research is qualitative which aims to identify the problems faced by students in the process of implementing PJOK learning at SMP 1 Batang Gansal. The research instrument used was an interview. The preparation of the interviews was carried out based on predetermined indicators, namely by breaking them down into question items, then producing statement items for the answers to the questions given by the author. Based on the results of the research, the conclusions obtained in this study are: the PJOK learning process at SMP Negeri 1 Batang Gansal is in accordance with the stages that must be carried out by the PJOK teacher, namely opening the lesson, apperception, warming up, explaining the material, giving examples and closing the lesson. But according to the results of interviews conducted by students, there were still some problems in the process of implementing PJOK learning that could hinder the student acceptance process. Whereas the factors that become a prominent problem are student factors, material factors and learning materials, method and strategy factors as well as facilities and infrastructure factors at SMP Negeri 1 Batang Gansal